2021
DOI: 10.1097/mao.0000000000003224
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Growing Sporadic Vestibular Schwannomas During Observation: An International Multi-Institutional Study

Abstract: Objective:Active treatment of small- or medium-sized vestibular schwannoma during wait-and-scan management is currently recommended at most centers globally once growth is detected. The primary aim of the current study was to characterize the natural history of growing sporadic vestibular schwannoma during observation.Study Design:Cohort study.Setting:Four tertiary referral centers across the United States and Denmark.Patients:Patients with two prior MRI scans demonstrating ≥2 mm of linear growth who continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…There is no internationally agreed or widely accepted management protocol resulting in great variability among different clinical centers (12). However, the advancement of clinical and diagnostic tools has increased the detection of tumors that are at an earlier stage and smaller in size (13); hence, many clinical centers have started to incline toward a more conservative approach; where a ''watch and wait'' protocol is implemented allowing to observe the tumor's natural history with successive magnetic resonance imaging scans, while active treatment with stereotactic radiosurgery (SRS) or surgical resection is reserved for larger tumors or in cases of evident tumor growth (14,15). Other factors playing a role in the decisionmaking process include the degree of hearing loss and patient's age, general condition, and preference (16,17).…”
mentioning
confidence: 99%
“…There is no internationally agreed or widely accepted management protocol resulting in great variability among different clinical centers (12). However, the advancement of clinical and diagnostic tools has increased the detection of tumors that are at an earlier stage and smaller in size (13); hence, many clinical centers have started to incline toward a more conservative approach; where a ''watch and wait'' protocol is implemented allowing to observe the tumor's natural history with successive magnetic resonance imaging scans, while active treatment with stereotactic radiosurgery (SRS) or surgical resection is reserved for larger tumors or in cases of evident tumor growth (14,15). Other factors playing a role in the decisionmaking process include the degree of hearing loss and patient's age, general condition, and preference (16,17).…”
mentioning
confidence: 99%
“…The incidence of VS was historically reported as 1 case per 100,000 before the development of MRI technology, but the actual incidence is much higher. As recently reported by Marinelli et al (1), the actual lifetime prevalence may be as high as 1 per 500 for sporadic VS.…”
Section: Introductionmentioning
confidence: 62%
“…This pattern was reproduced even after tumors were initially found to demonstrate growth, where 25% of tumors that had previously demonstrated growth had shown evidence of volumetric tumor regression after 5 years of additional follow-up with MRI. Unlike data examining the probability of future tumor growth (12,16,17), no feature examined in the current work reliably predicted future volumetric tumor regression. Lastly, although elevated rates of tumor shrinkage were observed when compared with previous linear tumor measurement studies, ultimately only 82 of the 952 patients studied exclusively demonstrated tumor shrinkage without growth at some point during the tumor's natural history.…”
Section: Discussionmentioning
confidence: 91%